(untitled) (Indian Journal of Arid Horticulture, 2017)
The wood apple (Feronia limonia Swingle) is a deciduous underutilized fruit tree belonging to the Rutaceae family. It is found mainly in forests and as individual ’stray plants’ in neglected areas. The ripe fruit has a sweet aromatic pulp with high nutraceutical properties. Additionally, its leaves, roots, and bark possess medicinal properties. These trees are typically grown with minimal care, and the application of manures and fertilizers is limited. The need for nutrient-feeding in underutilized fruit trees through organic manures and chemical fertilizers for sustainable fruit production is increasingly recognized (Ghosh, 2014; Ghosh and Bera, 2014; Sharath and Ghosh, S.N., 2015). NPK (Nitrogen, Phosphorus, and Potassium) are major nutrients required in large amounts, which vary according to the tree’s age, soil status, and climatic conditions. Leaf analysis is considered a realistic tool for studying a plant’s nutritional status (Bhargava, 1999), where foliar N, P, and K values can indicate plant health and productivity (Ghosh, 2014). The timing of leaf collection, specifically the maturity of leaves, and their position on the plant are crucial factors in leaf analysis. This investigation aims to address the lack of data on these aspects.